EKSTRAK AIR TANAMAN SELEDRI (APIUM GRAVEOLENS) TERHADAP PENINGKATAN VOLUME URIN TIKUS PUTIH - Adita Silvia Fitriana (Viva Medika, 2017)
ABSTRACT Processing of celery as diuretic is done by society in various ways. So far, the most effective preparation process of celery extract has not been known. This research aims to examine the diuretic effect of various celery extract preparation. This research was conducted using celery water extract which is made in accordance with the people’s habit, using aquades as a negative control and HCT as a positive control. The effectiveness test of celery water extract as diuretic was done on white male rat by measuring the urine volume every hour for six hours. The results showed that the largest urine volume is obtained from the boiling celery extract. Keywords: celery, diuretic, rat